PHENOMENON OF DEMIKHOV. In the Sklifosovsky Institute (1960–1986). Nomination as a Corresponding Member to the USSR Academy of Sciences (1966) - S. P. Glyantsev (Трансплантология (Москва), 2020)
The article has described, analyzed, and introduced into scientific circulation some previously unknown facts from V.P. Demikhov's life, namely, his nomination as a Corresponding Member to the USSR Academy of Sciences in the specialty "physiology" in May, 1966, and his experimental and research work in 1966. The inspection of his scientific activities undertaken on behalf of the Academic Council of N.V. Sklifosovsky Institute for Emergency Medicine, showed that the discoveries and achievements V.P. Demikhov had made in the field of physiology were significant, and he was worthy of being nominated for the rank of a Corresponding Member to the USSR Academy of Sciences. However, he lacked several votes for being elected to the Academy. Meanwhile, in 1966 V.P. Demikhov continued his unique research, having initiated studying the coronary blood flow of the transplanted heart, implementing immunosuppression in kidney transplantation, and starting the experiments on creating a bank of organs to preserve their functions before transplantation.